Chemical composition of the essential oil of Vitex rotundifolia L.F. from Vietnam - Thai, Tran Huy; Hong, Phung Tuyet; Minh, Do Thi (Academia Journal of Biology, 2014)
Vitex rotudinfolia L.f. (Verbenaceae) distributes at sand bands in many provinces of Vietnam. The yield of the essential oil from leaves and fruits of this shrub was 0.03 percent by air-dry material. This essential oil was analysed by GC/MS and 30 constituents of this oil were identified. The main constituents of this oil were: a-pinene (10.33%), sabinene (12.79%), camphene (15.51%), 1,8 cineol (19.38%) and trans-anethole (5.95%).